2012
DOI: 10.1186/1471-2393-12-49
|View full text |Cite
|
Sign up to set email alerts
|

In the Nepalese context, can a husband’s attendance during childbirth help his wife feel more in control of labour?

Abstract: BackgroundA husband’s support during childbirth is vital to a parturient woman’s emotional well-being. Evidence suggests that this type of support enables a woman to feel more in control during labour by reducing maternal anxiety during childbirth. However, in Nepal, where childbearing is considered an essential element of a marital relationship, the husband’s role in this process has not been explored. Therefore, we examined whether a woman in Nepal feels more in control during labour when her husband is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…Women whose husbands attended at ANC follow up were more likely to utilize the institution delivery service. This is also similar with the studies conducted in Tanzania, rural Bangladesh, and Nepal [16,[23][24][25][26][27][28][29]. Women, whose husbands attending with their own ANC follow NB ** P <0.001, * P < 0.05 and ***Not significant up, give opportunity for the husband access to health information.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Women whose husbands attended at ANC follow up were more likely to utilize the institution delivery service. This is also similar with the studies conducted in Tanzania, rural Bangladesh, and Nepal [16,[23][24][25][26][27][28][29]. Women, whose husbands attending with their own ANC follow NB ** P <0.001, * P < 0.05 and ***Not significant up, give opportunity for the husband access to health information.…”
Section: Discussionsupporting
confidence: 86%
“…This may give the chance for the women to communicate with their husbands about ANC follow up and place of birth. According to different literatures, women and their husbands should be given health education together, as this would result in a greater net impact on maternal health behaviors, compared to educating the women alone [26,27]. This might give the chance to men's to acquire knowledge about maternal health care and develop positive attitudes towards institution delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Scale for Measuring Maternal Satisfaction- Caesarean birth/SMMS-caesarean birth [44]Gungor & Beji (2012)TurkeyTo measure maternal satisfaction with birth in order to evaluate women’s experiences in labour and the early postpartum period before hospital discharge.See above.The Labor and Delivery Index/LADY-X [45]Gärtner et al (2015)The NetherlandsA utility measure for economic evaluations in perinatal studies.Developed to measure cost effectiveness of perinatal care interventions for use in research and is able to discriminate between groups [45]. The only instrument identified that measures economic evaluations in perinatal studies.The Labour Agentry Scale/LAS [46]Hodnett & Simmons-Tropea (1987)CanadaAn instrument measuring expectancies and experiences of personal control during childbirth.Since this scale was developed in 1987 [46] it has been used in studies from a broad range of countries as well as in different types of studies [8996]. Although widely used, further studies of the psychometric properties are recommended to ensure its validity and reliability.The Birth Satisfaction Scale - Revised/BSS-R [2729]Hollins Martin & Fleming (2011) Hollins Martin et al (2012)Hollins Martin & Martin (2014)UKTo measure postnatal women’s birth satisfaction.The birth satisfaction scale – revised [28] is a further development of the Birth satisfaction scale [27, 29, 97].…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian Story et al (2012) juga menemukan hal serupa bahwa dukungan emosional dan instrumental selama kehamilan memberikan pengaruh positif terhadap kehamilan dan persalinan. Sapkota et al (2012) juga mengemukakan bahwa dukungan peran suami dalam mendampingi istri menjalani persalinan menjadi penyebab istri merasa memegang kendali (feels more in control) selama persalinan. Dukungan peran suami pada lingkup domestik dikemukakan Utamidewi (2017) yang mengungkapkan bahwa kebahagiaan lebih terasa dalam rumah tangga ketika suami membantu istri melakukan pekerjaan rumah tangga.…”
Section: Pembahasanunclassified